Hyperbolic Time Discounting, Offender Time Preferences and Deterrence - Loughran, Thomas A. (Journal of quantitative criminology, 2012)
Objectives This study examines the phenomena of intertemporal decision making—decisions involving costs and benefits that occur at different points in time. Two models of intertemporal time discounting are the exponential and hyperbolic models. Previous work in behavioral economics and psychology is relied on to make the case that the discounting of delayed outcomes (both gains and losses) may be hyperbolic rather than exponential. Methods Data were collected from 478 university undergraduate students who responded to a hypothetical scenario involving drunk driving. The potential gains and losses of drunk driving were delayed at five different intervals from “tonight” to “10 years from now”, respondents were also asked to provide estimates of both the risk they would get caught if they did drink and drive and the probability that they would drink and drive under the conditions described in the scenario. Results Our results imply that individuals have hyperbolic time preferences for both rewards and gains, and that—unlike severity, the effect of which may be muted by risk—these discount functions appear to be operating independently of changes in the risk certainty of detection. Consistent with hyperbolic discounting, for example, when the benefit of drinking and driving was delayed by 1 week the self-reported intention to drink and drive increased by nearly 10%, however, when the gain was delayed by one month, intentions to drink and drive increased by only 4%. A smaller effect was found for delayed costs. Conclusions Avenues for additional research include the possibility of negative discount rates and the implications of persons’ awareness of their discount rates.